The The Implementation of Teaching Factory in Vocational Education: A Systematic Review - Rifai, Dede Syukrillah; Ardiansyah, Achmad; Yahya, Aliya Izet Begovic; Fitriyani, Riska (Jurnal VARIDIKA, 2026)
This study aims to comprehensively review the literature on Teaching Factory (TeFa) within vocational education, focusing on its role in narrowing the gap between classroom learning and industry demands. Through a Systematic Literature Review (SLR), the research synthesizes theoretical perspectives and empirical findings from peer-reviewed journals, conference papers, and other indexed publications published between 2020 and 2025. A structured screening and thematic coding process guided the selection of relevant works, enabling the identification of core variables, implementation strategies, and contextual factors shaping TeFa across countries. The review highlights that infrastructure readiness, teacher expertise, industry partnerships, and financial support influence successful TeFa practices. TeFa offers students authentic, industry-oriented experiences that strengthen technical and soft skills, thereby enhancing overall work-readiness. However, several challenges remain, such as resource limitations, uneven teaching practices, and the integration of digital manufacturing technologies. Moreover, gaps are evident in research concerning long-term digital factory planning, effective knowledge management, and data-based decision-making in vocational contexts. By systematically mapping these findings, this study advances the discourse on vocational education, offering evidence-based insights into the strengths, limitations, and future directions of TeFa. The results provide valuable input for educators, policymakers, and researchers to improve vocational education models, reinforce collaboration between schools and industry, and design sustainable frameworks for Teaching Factory implementation.